Bis repetita non placent: Griechische Finanzkontrolle im 19. Jahrhundert und in der Gegenwart - Korinna Schönhärl (IBF - Institut für Bank- und Finanzgeschichte, 2017)
– In June 2017, in the negotiations between Greece, the European Union and its Member States, the European Central Bank, and the International Monetary Fund, it was decided that the highly-indebted country in Europe's southern periphery should receive an additional disbursement of 8.5 billion euros from the 2015 aid package. The negotiations are another chapter in the endless disputes that have kept Europe in suspense since it first became apparent during the 2009 global economic crisis that Greece would no longer be able to service its foreign debt. One historical reference that the media repeatedly reported in this connection was the work of the International Finance Commission for Greece, which was established five years after Greek's bankruptcy in 1893 to ensure that Greece serviced its international debt. If one compares the Commission's work from 1898 with that of the troika in 2009, a number of parallels stand out: the actual or barely prevented sovereign default as the starting situation; the failure of all Greek attempts to get a handle on the situation without outside help, as well as the establishment of the commissions under extreme political pressure. There are also parallels with respect to the governance of the institutions: they were composed of politicians who protected the interests of private creditors and who could not always agree on a common strategy, as well as the restriction of Greek financial autonomy by foreigners. Most of the differences disappear however: The completely different global economic relationships at the end of the 19th and the beginning of the 21st century, the different natures of the Latin Monetary Union and the Eurozone, the large number of international and national political participants in the organizations with an equally broad range of different objectives, the different ways of working, and finally, the differences in the application of the conditionality principle.
Keywords: F34; N13; N14; N23; N24; O52; 330